Pengembangan Sistem Transportasi Pada Gudang In-Transit Merge Dengan Integrasi Sistem Android - Cahyo Prianto; Harun Ar-Rasyid; Nico Ekklesia Sembiring (Computer Engineering Departement, Universitas Komputer Indonesia, 2020)
The problem that arises in the business activities of companies that are based on the sale of goods is the lack of a system that can help companies carry out the activities of shipping goods from warehouses to stores. Therefore, in this project, a web-based and Android-integrated transportation and routing selection system will be developed. So that it can facilitate officers in choosing the type of transportation and also the driver in seeing the route.The function of selecting the type of transportation is very important to assist officers in selecting the type of transportation suitable for delivering goods. As well as with the routing function that can help the driver to find out the intended route. By developing this system, companies can easily access and monitor goods sent to the store and guarantee the safety of the goods sent will get to the store through the token feature. This application is designed using the PHP programming language and Code Igniter (CI) and MySQL framework as the database and UML as the analysis process and also integrates the Android system. This application can be accessed by super administrators, warehouse officers, staff, drivers, and shop owners who have registered in this application, which makes this application convenient for users to use. Keywords - Development; System; Warehouse; In-Transit Merge; Transportation.